Knowledge, Attitudes, and Practices Regarding Rabies in El Jadida Region, Morocco - Khadija Bouaddi; Abdelali Bitar; Mohammed Bouslikhane; Abdesslam Ferssiwi; Aziz Fitani; Philip Paul Mshelbwala (Veterinary Sciences, 2020)
The aim of this study was to evaluate the knowledge, attitudes, and practices regarding rabies in the El Jadida region, Morocco. We conducted a cross-sectional survey using a structured questionnaire among randomly selected residents across 24 study sites. In total, 407 respondents took part in the survey. The majority (367, 92%) were male and had no formal education (270, 66%). Some (118, 29%) believed that rabies does not affect humans. Most respondents (320, 79%) were aware that vaccination could prevent rabies, but nevertheless did not vaccinate their dogs (264, 64.9%) and allowed their dogs to roam freely in search of food. Some (52.8%) would visit traditional healers for treatment in the event of a dog bite incident. Age and educational level were found to be significantly associated with knowledge, attitudes, and practices (p < 0.05). Although respondents demonstrated some level of knowledge about rabies, overall this study reveals critical gaps in their attitudes and practices. These shortcomings may be associated with a low level of education. Therefore, decision-makers need a new approach to control rabies, with a special focus on public awareness and health education, in order to sustain rabies control programs.